Isolation and screening of halotolerant protease-producing bacteria from Lampung fermented shrimp paste - Istiadi, Khaerunissa Anbar; Ningsih; Suryanti, Erma; Imaniar, Lisana Husna (Bioeksperimen: Jurnal Penelitian Biologi, 2026)
Protease are class of degradative enzymes that hydrolyze proteins, breaking its peptide bond, into smaller peptides and amino acids. Microbial proteases have gained increasing attention due to its productivity and utilization in various industries. Proteolytic bacteria derived from fermented shrimp paste from Lampung have great potential to meet this need. However, studies on these bacteria are still limited, so further research is needed to explore and optimally utilize their potential. This study aims to explore the diversity of proteolytic bacteria from Lampung terasi.. The methods employed included isolation stages using Nutrient Agar supplemented with 5% and 10% NaCl (w/v), followed by proteolytic screening properties using Skim Milk Agar media. A total of 20 bacterial isolates were obtained from terasi using Nutrient Agar supplemented with 5% (w/v) NaCl, and 15 isolates were obtained from Nutrient Agar (NA)  supplemented with 10% (w/v) NaCl. Screening results showed that 85% and 67% of the isolates obtained from NA supplemented with 5% and 10% NaCl, respectively, exhibited proteolytic activity. Halotolerant bacterial isolates isolated using NA + 5% NaCl exhibited a proteolytic index ranging from 0.3 – 3.0, while those isolated with NA + 10% NaCl showed values ranging from 0.18 to 3.06. The screening results revealed that isolates BTCL5-07 and BTCL10-05 exhibited the highest proteolytic activity, with proteolytic indices of 3.0 and 3.06, respectively. These findings indicate that halotolerant bacteria from Lampung terasi represent a promising source of potential proteolytic enzymes. Further research is required to optimize enzyme production.